Diversity and Abundance of Local Butterflies (Order Lepidoptera) in Ternate - Drakel, Nelly Ardiani; Mas’ud, Abdu; Ahmad, Zulkifli; Sundari, Sundari (SAINTIFIK@: Jurnal Pendidikan MIPA, 2025)
Ternate Island has a forest ecosystem rich in biodiversity, including butterflies that play an essential role as natural pollinators and biological indicators of Environmental Health. However, pressures from human activities, such as deforestation, land conversion, and the disposal of inorganic waste, lead to habitat degradation, loss of host plants, and a decline in butterfly populations. This study aims to provide the latest information on the diversity and abundance of local butterfly species on Ternate Island, informing conservation efforts. The research employs an exploratory descriptive approach, utilizing a time search method with a wide search radius of 100 m at each research location. The research results found 351 individuals consisting of 18 types of local butterflies from 4 families, namely; 1) family Nymphalidae with 11 species including Cyrestis acilia, Danaus genutia, Ideopsis vulgaris, Elymnias hypermnestra, Mycalesis terminus, Parantica cleona, Pantopria hordonia, Danaus affinis, Hypolimnas bolina, Ideopsis vitrea, and Euploea tulliolus 2) the Pieridae family of 3 species includes Eurema hecabe, Catopsilia pyranthe, and Catopsilia scyll 3) the Lycaenidae family includes one species Lampides boeticus 4) Family Papilionidae with three species including Pachliopta polyphontes, Troides criton and Troides helena etc. The value of the local butterfly diversity index in Ternate Island is H’ = 2.32.32, which is categorized as moderate diversity. Furthermore, the abundance index analysis yields a value of 100%, which is classified as very high abundance.